Analisis Kesadaran Merek dan Kepuasan Pelanggan ( Studi Kasus pada Pengguna Aplikasi Pembayaran Elektronik PT. Visionet Internasional OVO) di Palembang) - Yuliyana Yuliyana; Fakhry Zamzam; Luis Marnisah (Integritas Jurnal Manajemen Profesional (IJMPRO), 2020)
This research is a qualitative method research, it is conducted to analyze brand awareness and customer satisfaction from one of the FINTECH OVO electronic payment application systems. In analyzing the brand awareness, there are top of mind indicators, brand recall, brand recognition, and unware brand. Meanwhile, to analyze customer satisfaction with 5 indicators namely, tangibles, reliability, responsiveness, assurance and empathy. Those are analyzed by using direct interviews to customers and in analyzing companies, namely PT. International Visionet uses SWOT analysis and SWOT matrix. In this research, there were 100 samples, with the location of the distribution of questionnaires dissemination in several locations of shopping centers, offices and universities in Palembang city. Based on the results of interviews with OVO customers, the results on brand awareness and customer satisfaction were divided into several groups, namely from the grouping of respondents by age, occupation, education address and gender. In the brand awareness variable, 70% of customers were aware of the product in terms of top of mind indicators, 77.25% brand recall, 93% brand recognition and 73.5% unware brand. Meanwhile, for the customer satisfaction variable the results obtained were tangibles 83%, reliability 95.75%, responsiveness 74.5%, assurance 94% and empaty 55%. For the analysis at PT. Visionet International, the results of a SWOT analysis using the SWOT matrix and Cartesian diagrams, the results of the analysis showed that an X axis was 0.8 and a Y axis was 0.7. Therefore, based on the research findings, it showed that the strategy which must be done by the company was to use the company's strength strategy and to take advantage of opportunities that exist in the company.